Prediabetes, diabetes, and the risk of progression to diabetes among working population in Beijing-the Tongren HealthCare Study - Yu Li; Wen Liu; Xuemei Zeng; Jing Cui; Dongning Chen; Yu Wang; Xi Cao (PLoS ONE, 2026)
Introduction Our retrospective cohort study (3–9 years) describes the progression and regression patterns among working adults aged 18–65 with normoglycemia, prediabetes, and diabetes, providing evidence for diabetes prevention and management strategies in this population. Research design and methods 15,765 subjects received baseline examinations between 2014 and 2018, with 14,623 (92.7%) completing follow-up, representing a follow-up period of 3–9 years for analysis. Chi-square tests were used to compare prediabetes and diabetes incidence, as well as rates of glycemic normalization among different age groups and genders in working populations. Cox proportional hazard regression models were used to estimate hazard ratios (HRs) and 95% confidence interval (CI). Results Among participants with baseline normoglycemia, 23.9% progressed to prediabetes, and 2.3% developed diabetes. Among prediabetic individuals, 28.0% progressed to diabetes, and 18.7% reverted to normoglycemia. Younger adults (18–40 years) exhibited significantly lower progression rates from normoglycemia to both prediabetes and diabetes compared to middle-aged adults (40–65 years) (prediabetes: 15.8% vs. 37.8%; diabetes: 1.2% vs. 4.2%; P < 0.001). Cox models revealed that young prediabetic individuals had a significantly higher risk of developing diabetes than middle-aged prediabetic individuals, showing a pronounced age-dependent risk pattern: prediabetic individuals aged 18–40 had an adjusted hazard ratio (HR) of 22.1 (95% CI: 14.9–32.7), compared to HR = 9.12 (7.45–11.2) in those aged 40–65. Conclusions Prediabetes among working-age adults, particularly in younger individuals (18–40 years), carries an exceptionally elevated risk of progression to diabetes. The observed sex disparities in progression among young adults highlight the need for age- and sex-specific prevention strategies.